Analysis of the Queuing System in XYZ Food Industry in Batam City (Case Study of Queuing Time Observation) - Putera, Dimas Akmarul; Dermawan, Aulia Agung; Lawi, Ansarullah; Saputra, Puji Tri; Pane, Amirah Nova Khairiyah; Maulidina, Siti Nur (Jurnal Sistem Teknik Industri, 2024)
This study analyzes the queuing system at XYZ fast food restaurant in Batam City to improve service efficiency and customer satisfaction. Observations were conducted over eight hours on Saturday, April 6th, 2024, from 2:00 PM to 10:00 PM. Data collected included arrival patterns, service time, and customer wait time. Using the queuing model [M/G/2/FIFO/4/âˆž], it was found that two servers are optimal. The average customer wait time in the system is 4.938 minutes, which is lower than the customer's aspirational wait time of 10 minutes. The system's utility reachedÂ  84.33%, indicating sufficient efficiency. Practical recommendations for XYZ fast food restaurant management are to maintain two servers to reduce wait time and increase customer satisfaction.